Implementasi Kebijakan Sertifikasi Guru di Kota Tangerang Selatan - Farriha Azkia Hanum; Nida Handayani (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Teacher certification is carried out through the Teacher Professional Education Program (PPG) which is organized by universities determined by the Minister. However, in its implementation there are still problems, including a lack of socialization regarding in-service teacher certification policies and complex teacher certification procedures and limited quotas. The purpose of this research is to determine the implementation of the Teacher Certification Policy in South Tangerang City. The method used in this research is a qualitative approach with descriptive methods. Data collection methods were carried out by interviews, observation and documentation. The theory used in this research is the Implementation Model according to Charles O Jones which consists of Organization, Interpretation and Application. The results of this research explain that the organizational indicators related to resources are that the implementation of this policy has not run optimally, there is a lack of training and coaching for implementing staff. The interpretation of the implementation of the teacher certification policy has provided clarity regarding the goals and objectives of all parties involved in implementing the policy. The implementation of this policy is going well, the Government provides the SIMPKB platform which contains complete information about PPG for pursuing an educator certificate.